The patient-doctor relationship – a psychological perspective - Śliwińska, Zofia; Makara-Studzińska, Marta; Śliwiński, Zbigniew (Medical Studies/Studia Medyczne, 2015)
This review of available literature aims to present models of co-operation between the patient and the doctor, the consequences of employing these models, and the ways of building relationships. In order to ensure a comprehensive view of this issue and trace the dynamics of changes in this area, we decided to review the relevant literature published since the 1950s. The databases we queried contained academic opinion papers, reports of empirical studies, and publications in psychology of health. Used databases: Academic Search Complete, eBook Academic Collection, Health Source: Nursing/Academic Edition, MEDLINE, PsycARTICLES, and PsycINFO. The analysis focused on the association between the models of patient-doctor relationship and adherence to treatment ( adherence or compliance; adherence to treatment ). The paper contains descriptions of how models have changed, followed by a detailed characterisation of the paternalistic and partnership-based approaches, also with regard to possible effects on the patient’s willingness to adhere to medical instructions.